A composite inorganic floor material
By using composite inorganic floor materials, including new micro-expanding agents and other additives in the inorganic grinding stone floor, the problem of easy cracking during the molding and hardening process is solved, and high compressive and tensile strength and good Crack resistance.
Patent Information
- Application Number
- CN202411572245.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing inorganic grinding stone floors are prone to shrink and cracking during the molding and hardening process, and cracking is also prone to occur when the strength is insufficient.
A composite inorganic floor material is used, including silicate cement, aggregate, blast furnace iron sludge, crack-resistant fibers, glass powder, activators and new micro-expanding agents. Among them, the micro-expanding agent is made of lithium slag and red mud, and is produced by crushing, granulating and sintering processes, and has good micro-expanding properties.
This composite inorganic floor material has high compressive strength and tensile strength, and has a certain micro-expansion performance. It can maintain a relatively gentle micro-expansion rate during the curing cycle, significantly improving crack resistance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to a composite inorganic floor material. Background Art
[0002] Inorganic terrazzo flooring is an excellent flooring material, surpassing existing terrazzo flooring in strength and early strength. Furthermore, inorganic terrazzo flooring can be laid seamlessly throughout, resulting in a more aesthetically pleasing overall appearance. Existing terrazzo floors, on the other hand, often require stripping to prevent cracking, resulting in numerous gaps and a less aesthetically pleasing appearance.
[0003] However, for inorganic terrazzo floors, cement is usually used as the gelling material, and cement is prone to shrinkage and cracking during the molding and hardening process; at the same time, when the floor material is not strong enough, it is also prone to cracking. Summary of the Invention
[0004] In view of the above technical problems, the purpose of the present invention is to provide a composite inorganic floor material to address the defects of the prior art.
[0005] The present invention adopts the following technical solution: a composite inorganic floor material, which comprises, by mass: 30 to 50 parts of Portland cement, 80 to 120 parts of aggregate, 15 to 25 parts of blast furnace iron smelting slag, 0.5 to 2 parts of anti-cracking fiber, 5 to 10 parts of glass powder, 4 to 10 parts of activator, and 10 to 15 parts of micro-expansion agent;
[0006] The preparation method of the micro-expanding agent comprises the following steps: taking 50-55 parts of lithium slag and 38-45 parts of red mud, crushing them, adding 20-25 parts of water, stirring them evenly, then granulating them, and then sintering them at 700-800°C for 2-4 hours. After sintering, the mixture is naturally cooled to room temperature, and then crushed to obtain the micro-expanding agent.
[0007] In the present invention, a new micro-expansion agent is proposed to address the problem that conventional inorganic floors are prone to cracking. The micro-expansion agent is made from industrial solid waste. For lithium slag, it contains a large amount of silicon dioxide, aluminum oxide and calcium oxide, among which silicon dioxide and aluminum oxide exist in amorphous form. The main components of red mud are aluminum oxide, silicon dioxide, iron oxide and calcium oxide, and it also contains a certain amount of non-ferrous metals. After the two are crushed, granulated and sintered, the final product has good micro-expansion performance. And compared with conventional calcium oxide and magnesium oxide expansion agents, the expansion agent of the present invention has a long micro-expansion time, and the expansion multiple is relatively low in a short time, which will not affect the floor.
[0008] Aggregate is also called aggregate. The aggregate in the present invention is conventional aggregate in the floor field. Generally speaking, aggregate is divided into fine sand, medium sand and fine sand, all of which can be applied to the present invention.
[0009] Blast furnace iron smelting slag is a cementitious material, a solid waste, and can also be used as an aggregate. Compared to cement, its advantage is that the particle size can be freely adjusted. Depending on the particle size, the product after gelation and solidification has different micropores, which makes the floor material have certain air permeability. At the same time, when added to cement, it can also serve as a condensation nucleus for the initial hydration of cement, thereby accelerating the hydration process of cement. Generally speaking, it needs to be used together with an activator to quickly promote the hydration and gelation of blast furnace iron smelting slag.
[0010] One embodiment of the present invention is that the aggregate is medium sand.
[0011] One embodiment of the present invention is that the aggregate is a mixture of medium sand and fine sand, and the mass ratio of the medium sand to the fine sand is 8:2~5.
[0012] One embodiment of the present invention is that the particle size of the blast furnace iron smelting slag is not greater than 2 mm. The larger the particle size, the lower the flatness of the floor, the lower the strength, the greater the difficulty of hydration, and the worse the crack resistance. The smaller the particle size, the higher the flatness of the floor, the greater the final strength, the less difficult it is to hydrate, and the better the crack resistance. In fact, when the specific surface area of the blast furnace iron smelting slag reaches 300m 2 / kg, its hydration basically does not require an activator. However, in actual production, the larger the specific surface area, the higher the production cost. Therefore, after extensive experiments, the inventors found that when the particle size of blast furnace iron smelting slag is no more than 2mm, the floor has higher flatness and higher compressive strength, which can meet actual use requirements.
[0013] In one embodiment of the present invention, the crack-resistant fiber is basalt fiber. In fact, a wide range of fibers can be used in this invention, such as polypropylene fiber and glass fiber. However, in actual use, basalt fiber has a longer lifespan than polypropylene fiber and is less harmful to the human body than glass fiber.
[0014] One embodiment of the present invention is that the activator is at least one of sodium hydroxide, sodium carbonate, and water glass.
[0015] One embodiment of the present invention is that the floor material includes: 30 to 35 parts of silicate cement, 80 to 95 parts of aggregate, 15 to 20 parts of blast furnace iron smelting slag, 0.5 to 0.8 parts of anti-cracking fiber, 5 to 10 parts of glass powder, and 10 to 12 parts of micro-expansion agent.
[0016] One embodiment of the present invention is that the floor material includes: 38 to 42 parts of silicate cement, 100 to 110 parts of aggregate, 18 to 22 parts of blast furnace iron smelting slag, 1 to 1.5 parts of anti-cracking fiber, 7 to 8 parts of glass powder, and 12 to 15 parts of micro-expansion agent.
[0017] One embodiment of the present invention is that the floor material further includes 15 to 25 parts of inorganic pigments, and the inorganic pigments are at least one of titanium dioxide, phthalocyanine green G, and iron oxide.
[0018] One embodiment of the present invention is that the blast furnace iron smelting slag is modified by the following method before use: 10-18 parts of pseudo-boehmite are added to 40-70 parts of water, followed by acid addition and continuous stirring for at least 10 minutes to form a pseudo-boehmite sol, followed by addition of 150-200 parts of blast furnace iron smelting slag and stirring at 200-1000 rpm and 50-80°C for at least 10 minutes, followed by drying after stirring; the amount of acid added is 0.5-3 parts. The modified blast furnace iron smelting slag has better performance and the resulting floor has higher strength.
[0019] The present invention has the following beneficial effects: the composite inorganic floor material of the present invention has high compressive strength and high tensile strength, and the concrete floor of the present invention has a certain micro-expansion performance, and the micro-expansion rate within the floor curing period (28 days) is relatively gentle. These characteristics make the floor material of the present invention have good crack resistance. DETAILED DESCRIPTION
[0020] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of implementation of the present invention.
[0021] In the following examples, unless otherwise specified, the operations described are routine operations in the art.
[0022] In the following examples, unless otherwise specified, all raw materials used are conventional commercial products in the art.
[0023] In the following examples, unless otherwise specified, the parts are by mass.
[0024] Example 1: Preparation of a micro-expanding agent: 51 parts of lithium slag and 40 parts of red mud were crushed and stirred to mix them evenly. 22 parts of water were then added and stirred to mix them evenly. The pellets were then granulated into pellets using a granulator. The pellets were placed in a sintering furnace, heated to 750°C and kept warm for 3 hours. After the insulation was completed, the sintered pellets were naturally cooled to room temperature and then crushed to pass through a 20-mesh sieve.
[0025] Modification of blast furnace iron smelting slag: Take 15 parts of pseudo-boehmite and add it to 60 parts of water, stir to make it evenly dispersed, add 2.5 parts of concentrated hydrochloric acid under continuous stirring and continue stirring for 10 minutes. After stirring, add 180 parts of blast furnace iron smelting slag (passed through an 18-mesh sieve) and stir at 600r / min and 60℃ for 15 minutes. After stirring, dry it.
[0026] The composition of the composite inorganic floor material: 40 parts of Portland cement (grade 42.5), 105 parts of aggregate (medium sand and fine sand in a mass ratio of 8:3.5), 20 parts of modified blast furnace iron smelting slag, 1.4 parts of basalt fiber, 7.5 parts of glass powder, 18 parts of titanium dioxide, and 14 parts of micro-expansion agent.
[0027] Example 2: Compared with Example 1, the difference is that the blast furnace iron smelting slag is not modified, and 6 parts of activator sodium hydroxide are added to the floor material, and the rest are the same.
[0028] Example 3: Preparation of micro-expanding agent: Take 54 parts of lithium slag and 44 parts of red mud, crush them, stir them to mix them, then add 24 parts of water, continue stirring to mix them, and then use a granulator to granulate them. The formed particles are placed in a sintering furnace, heated to 780°C and kept warm for 3 hours. After the insulation is completed, the sintered particles are naturally cooled to room temperature and then crushed to pass through a 20-mesh sieve.
[0029] Modification of blast furnace iron slag: Take 12 parts of pseudo-boehmite and add it to 60 parts of water. Stir until it is evenly dispersed. While stirring continuously, add 1 part of concentrated sulfuric acid and continue stirring for 15 minutes. After stirring, add 160 parts of blast furnace iron slag and stir at 400 rpm and 55°C for 30 minutes. After stirring, dry the mixture.
[0030] The composition of composite inorganic floor materials: 32 parts of silicate cement (grade 42.5), 90 parts of aggregate (medium sand), 16 parts of modified blast furnace iron smelting slag, 0.7 parts of basalt fiber, 6 parts of glass powder, and 11 parts of micro-expansion agent.
[0031] Example 4: Compared with Example 1, the difference is that the basalt fiber is replaced by polypropylene fiber, and the rest are the same.
[0032] Example 5: Compared with Example 1, the difference is that the particle size of blast furnace iron smelting slag is 2~5mm, and the rest are the same.
[0033] Comparative Example 1: Compared with Example 1, the difference is that SRM high-performance concrete expansive agent (calcium oxide type) is used instead of the micro-expansive agent, and the rest are the same.
[0034] Comparative Example 2: Compared with Example 1, the difference is that 14 parts of micro-expansive agent are replaced by a mixture of 7.8 parts of lithium slag and 6.2 parts of red mud, and the rest are the same.
[0035] In order to further illustrate the advantages of the embodiments of the present invention, they are described below with reference to specific experimental data.
[0036] 1. Strength and water absorption test
[0037] The floor compositions of Examples 1-7 and Comparative Examples 1-2 were added with water to form concrete floors. These floors were then cured at room temperature. The compressive strength and water absorption were measured at regular intervals. The results are shown in Table 1. The testing methods are described in GB / T 50081-2019, "Test Methods for Physical and Mechanical Properties of Concrete." When the concrete floors were prepared, the water-cement ratio was 0.33.
[0038] Table 1 Strength change and water absorption test results at different times
[0039]
[0040] It can be seen from Comparative Document 1 that the floor composition of the embodiment of the present invention has high compressive strength, high tensile strength and low water absorption; at the same time, the concrete floor made from the floor composition of the embodiment of the present invention still has a considerable increase in strength after the curing age (28d).
[0041] 2. Micro-expansion performance test
[0042] Referring to GB50119-2013 "Technical Specification for the Application of Concrete Admixtures", the micro-expansion performance of the flooring materials of Examples 1-5 and Comparative Examples 1-2 was tested, and the final results are shown in Table 2. Among them, when configured as a concrete floor, the water-cement ratio is 0.33; the blank refers to the floor configured without the micro-expansion agent material.
[0043] Table 2 Expansion rate test table
[0044]
[0045] It can be seen from Table 2 that the composite inorganic floor material according to the embodiment of the present invention has good micro-expansion performance.
[0046] Referring to Examples 1 to 5, it can be seen that the composite inorganic floor material of the embodiment of the present invention has a certain micro-expansion performance during the hardening stage of the floor, and the degree of micro-expansion is low, and it can continue to expand, which is manifested in that the difference in expansion rate after 14 days in water and 28 days in air after 14 days in water is small, indicating that the composite inorganic floor material of the embodiment of the present invention can still continue to micro-expand in the air.
[0047] Referring to Example 1 and Comparative Example 1, it can be seen that compared with conventional expansion agents available on the market, the expansion agent of the embodiment of the present invention has better performance, and the volume change rate of the floor in water and air is lower, thereby reducing the probability of microcracks in the floor caused by shrinkage.
[0048] Referring to Example 1 and Comparative Example 2, it can be seen that although lithium slag and red mud used alone have certain micro-expansion properties, the performance is relatively poor.
[0049] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A composite inorganic floor material, characterized in that: In parts by mass, it includes: 30-50 parts of Portland cement, 80-120 parts of aggregate, 15-25 parts of blast furnace iron smelting slag, 0.5-2 parts of anti-cracking fiber, 5-10 parts of glass powder, and 10-15 parts of micro expansion agent; The preparation method of the micro-expanding agent comprises the following steps: taking 50-55 parts of lithium slag and 38-45 parts of red mud, crushing them, adding 20-25 parts of water, stirring them evenly, then granulating them, and then sintering them at 700-800° C. for 2-4 hours, and then naturally cooling them to room temperature after the sintering, and then crushing them to obtain the micro-expanding agent; The particle size of the blast furnace iron smelting slag is not more than 2 mm, and the floor material also includes 4 to 10 parts of an activator; The blast furnace iron smelting slag is modified by the following method before use: 10-18 parts of pseudo-boehmite are taken and added to 40-70 parts of water, followed by adding acid and continuously stirring for at least 10 minutes to prepare pseudo-boehmite sol, followed by adding 150-200 parts of blast furnace iron smelting slag and stirring at 200-1000r / min and 50-80°C for at least 10 minutes, and drying after the stirring is completed; the amount of acid added is 0.5-3 parts.
2. The composite inorganic floor material according to claim 1, characterized in that: The aggregate is medium sand.
3. The composite inorganic floor material according to claim 1, characterized in that: The aggregate is a mixture of medium sand and fine sand, and the mass ratio of the medium sand to the fine sand is 8:2-5.
4. The composite inorganic floor material according to claim 1, characterized in that: The anti-cracking fiber is basalt fiber.
5. The composite inorganic floor material according to claim 1, characterized in that: The activator is at least one of sodium hydroxide, sodium carbonate and water glass.
6. The composite inorganic floor material according to claim 1, characterized in that: The floor material includes: 30-35 parts of silicate cement, 80-95 parts of aggregate, 15-20 parts of blast furnace iron smelting slag, 0.5-0.8 parts of anti-cracking fiber, 5-10 parts of glass powder, and 10-12 parts of micro-expansion agent.
7. The composite inorganic floor material according to claim 1, characterized in that: The floor material includes: 38 to 42 parts of silicate cement, 100 to 110 parts of aggregate, 18 to 22 parts of blast furnace iron smelting slag, 1 to 1.5 parts of anti-cracking fiber, 7 to 8 parts of glass powder, and 12 to 15 parts of micro-expansion agent.
8. The composite inorganic floor material according to claim 1, characterized in that: The floor material also includes 15 to 25 parts of inorganic pigments, and the inorganic pigment is at least one of titanium dioxide, phthalocyanine green G, and iron oxide.
Citation Information
Patent Citations
Concrete expansion agent based on industrial waste and preparation method of concrete expansion agent
CN108793798A
Inorganic composite gel system
CN113372899A
Self-compacting terrace material
CN117466609A
Solid binding agent for environment-friendly refractory material and preparation method of solid binding agent
CN118619597A